PEMANFAATAN ANALISIS BIAYA VOLUME LABA SEBAGAI ALAT DALAM PERENCANAAN LABA PADA PT INKO JAVA SEMARANG - Syafira Rosyalia; Lardin Korawijayanti; Hartono - (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2019)
Cost profit volume analysis is a tool used by management to do a shortterm profit planning by using an approach to costs, volume of sales, and profits. The purpose of its research is to determine the application of the analysis of cost volume profit at PT Inko Java Semarang in profit planning with the calculation of contribution margin, contribution margin ratio, break-even point, the analysis of the profit target, margin of safety, degree of operating leverage, shut down point, and sensitivity analysis. Data that used in this final project is secondary data consist of the sales and costs data in 2017. Data collection was obtained by interview and documentation. The writing method thatused are description and exposition method. The results of this research showed that break-even point was at the sales value of Rp 51.560.373.141,52 or 148.868 units with an average contribution margin per unit of Rp 41.217,04and contribution margin ratio amounted to 11,90%. The profit target set at 1% of the sales in 2017. To reach the expeceted profit, the volume of sales must be Rp 55.520.899.913. Margin of safety are Rp 3.960.526.771,48or by 7,13% and the degree of operating leverage amounted to 11,90. Shut down point occurs at the level of sales of Rp 45.823.939.568,56.